Political drivers of and barriers to Public-Private Partnerships: The role of political involvement - Erik Gawel (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2011)
The application and design of public-private partnerships between the extremes of purely public or purely private task fulfilment in public services is, in practice, subject to political processes. Decisions about PPPs (realisation, arrangement) are taken in the political arena and are therefore not theoretical optimisation exercises. The interests and resources of the actors who participate in the political decision-making process as well as the rules of the political process have a powerful influence on whether, in what areas, and in what form PPPs are realised. The distance between this output and solutions that are theoretically desirable given certain ideal goals (e.g. efficiency) and conditions can be referred to as political bias. So what role does the political process play in the realisation of PPPs, in the actual design of PPPs, and in their performance? Using public choice and institutional economics theory this paper analyses what chances of success PPPs have given the existing decision-making structures and the inherent incentives for participating actors, and in what way political influence is brought to bear in the first place. Furthermore, aspects of political science in this field (legitimacy, democratic control) are considered as well. Using PPPs there might be a trade-off between reduced democratic control, but also reinforced market control. It turns out that political involvement might be both an important driver as well as an obstacle for (efficient) PPPs and that it is likely to decrease efficiency either way. A case study for userfinancing PPPs in the transport sector highlights the problems of political renitency.
Keywords: D72; D73; D78; H11; H44; H63; H83; 330; public-private partnership; politics; bureaucracy; public choice; contract theory; agency; tax state; transaction cost; governance; legitimacy; transport infrastructure; user financing